I have three more than you, you have three less than me? Levels of flexibility in dealing with additive situations - Ufer, Stefan; Kaiser, Anna; Niklas, Frank; Gabler, Laura (Frontiers in Education, 2024)
Assessment and intervention in the early years should ideally be based on evidence-based models describing the structure and development of students' skills. Mathematical word problems have been identified as a challenge for mathematics learners for a long time and in many countries. We investigate flexibility in dealing with additive situations as a construct that develops during grades 1 through 3 and contributes to the development of students' word problem solving skills. We introduce the construct based on prior research on the difficulty of different situation structures entailed in word problems. We use data from three prior empirical studies with N = 383 German grade 2 and 3 students to develop a model of discrete levels of students' flexibility in dealing with additive situations. We use this model to investigate how the learners in our sample distribute across the different levels. Moreover, we apply it to describe students' development over several weeks in one study comprising three measurements. We derive conclusions about the construct in terms of determinants of task complexity, and about students' development and then provide an outlook on potential uses of the model in research and practice.